Morphological characterization and DNA barcoding of Ruellia sp. in Saudi Arabia - Jawaher Saad Almuteri; Mona Soliman Al wahaibi; Abd El-Zaher Mohamad Mustafa; Manal Abdullah Alshaqhaa; Muhammed Afzal; Manar Dhafer Alshehri (PLoS ONE, 2025)
The genus Ruellia L. belongs to this family and its plants are herbs or shrubs. This genus was first detected in the tropical and subtropical regions. The primary objective this study is to identify the various species within the genus Ruellia using both morphological characteristics and DNA barcoding methods. For this purpose, plant samples were meticulously collected from eight distinct natural habitats across the region. All vegetative and floral parts were examined using a binocular microscope. All parts are measured and photographed. To ensure accurate identification and characterization, four molecular barcoding markers were employed: Psbk-psbi, trnH-psbA, rbcL, and AtpF-AtpH. Eight Ruellia species were identified from different regions: Abha, Aseer (24651), Jazan (24652), Malacosperma, Patula, Taif (24650 rose), Taif (24650 violet), and Taif (24650 white). The species were confirmed using specimens from the King Saud University herbarium. Notably, the samples collected from Taif, which had flowers of different colors, were determined to represent a single species with different genotypes. The use of four DNA barcode markers (Psbk-psbi, trnH-psbA, rbcL, and AtpF-AtpH) facilitated the identification of five distinct species: R. tweediana, R. sp. SH2010, R. carolinensis, R. simplex, and R. patula. These findings confirmed the dominant Ruellia species in Saudi Arabia and demonstrated the reliability of DNA barcode markers for species identification. Further assessment of these species’ adaptability, molecular genetics, and functional genomics is necessary for their commercial utilization in the region. These species are recorded for the first time in Saudi Arabia and represent the first record.